PENERAPAN KECERDASAN TIRUAN UNTUK MONITORING TEGANGAN PADA SOLAR CELL - Ridho’i, Ahmad; Yuliananda, Subekti; Andriawan, Aris Heri (JHP17 (Jurnal Hasil Penelitian), 2016)
The use of renewable energy is needed to reduce the energy crisis,renewable energy is very abundant in the earth of which the sun as a source ofenergy. To support the process of conversion of energy the sun into electricitytakes place either required maintenance and monitoring in order to obtainmaximum energy sources. Among them caused by dust, leaves, exposed to thedust and water, the contamination by dust surface will be disturbed solar cellenergy conversion is generated. The application of intelligence method is oneway to solve these problems. In addition the use of artificial intelligence forverification whether the intelligence methods are more effective and simpler insolving the problem of monitoring. Therefore we need some variables includevoltage, brightness, and time, to support a process that uses artificialintelligence methods. By utilizing the microcontroller ATMega8535 asprocessing for artificial intelligences methods provide a more concrete and theuse of software (Matlab, Proteus) for simulation.Keywords: artificial intelligence